Práticas corporais complementares: um estudo sobre a antiginástica - Santos, Thais Yuri Jo [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The concept of physical education emerged in the XIX century through the European gymnastic methods, initially for the purpose of asserting the sovereignty of the nationality of countries, by means of exaltation of patriotism of the masses and the physical preparation for military wars. Nowadays, the cult of the ideal body has changed, becoming the unceasing desire within each society, according to its characteristics of established standards, most of the time denying the genetic determinations of each ethnicity. This social phenomenon has generated openness and encouragement to the fitness market on the rise, eager in supporting the aspirations of the cult of the body”, representing the huge seek of the idea of a healthy body and an aesthetic appearance acceptable in today's society. Parallel to this, the Body Awareness Gymnastics, also known as Technical or Complementary Practices, were introduced in Brazil in the 70s, presenting as main themes the body awareness, the mind-body relationship, and against the ideals of body training. According to authors, the pioneering technique of the movements of alternative practices in Brazil was Antiginástica of Thérèse Bertherat. Therefore, this study aims to harmonize the complementary body practices of the physical education area through literature review of published works by the author Thérèse Bertherat, entitled The body has its reasons, The body communication system, Stations of the body, The Tiger´s Den and When the body is consent. The work also includes the contribution of a particular reading of the researcher, from the experiences of the practices carried out in order to enrich the reporting work through their records, the results obtained from the experiential process

O conceito de educação física surgiu no século XIX através dos métodos ginásticos europeus, primeiramente com a finalidade de afirmar a soberania de nacionalidade dos países, por meio da exaltação do patriotismo das massas e a preparação física militar para as guerras. Atualmente, mudou-se o ideal de culto ao corpo, que tornou-se o desejo incessante dentro de cada sociedade, de acordo com suas características de padrões estabelecidos, negando na maioria das vezes as determinações genéticas de cada etnia. Este fenômeno social gerou abertura e incentivo para o mercado fitness em ascensão, desejosos em respaldar os anseios do “culto ao corpo”, representando a enorme busca pela ideia de corpo saudável e de uma aparência estética aceitável pela sociedade atual. Paralelo a este quadro, as Ginásticas de Conscientização Corporal, também conhecidas por Técnicas ou Práticas Complementares, foram introduzidas no Brasil na década de 70, apresentando como temas principais a consciência corporal, a relação corpo-mente, e contra os ideais de adestramento corporal. Segundo autores, a técnica pioneira dos movimentos das práticas alternativas no Brasil foi a Antiginástica de Thérèse Bertherat. Sendo assim, este trabalho tem por objetivo aproximar as práticas corporais complementares da área da Educação Física através da revisão de literatura das obras publicadas da autora Thérèse Bertherat, intituladas “O corpo tem suas razões”, “O correio do corpo”, “As estações do corpo”, “A toca do tigre” e “Quando o corpo consente”. O trabalho ainda conta com a contribuição de uma leitura particular da pesquisadora, a partir das vivências das práticas realizadas a fim de enriquecer o trabalho relatando através de seus registros, os resultados do processo vivencial obtido
Keywords: Ginástica; Corpo e mente; Medicina alternativa; Ginásticas de conscientização corporal